New and obscure species of the genus Chilocorus Mayr in eastern Asia, with the proposal of a "nitidus-group" concept (Hemiptera: Heteroptera: Cydnidae) - Imura, Jimpei (Zootaxa, 2011)
Comments are presented on four East-Asian species of the genus Chilocoris Mayr, of which three are known but have been hardly mentioned―namely C. alienus Horváth, C. birmanus Lis and C. nitidulus Lis. One new species is described here as C. monticola n. sp. New distribution records are provided: C. alienus is new to China (Liaoning), as well as newly representing the genus in northern China; C. birmanus is new to Taiwan; and C. nitidulus is new to Vietnam and Thailand. Until recently, C. monticola n. sp. found in Japan has been misidentified as C. nitidus Mayr, and earlier records of the latter from Japan are really this new species. Male genital structures are described and illustrated for all four species, and additionally female genital structures are also described for C. birmanus and C. monticola. These East-Asian species are significantly similar to each other in important morphological structures such as the pronotal punctuation, extension of evaporatorium, and the male and female genital organs, yet they can be distinguished from many other congeners by these same structures. It seems plausible, therefore, to group these four species in a species-group named “nitidus-group” because of the species’ definite association with C. nitidus. This species-group possibly consists at least ten East-Asian and one North American species and exhibits a relictual, trans-Beringian disjunction, suggesting an association of this group with the Tertiary circum-boreal flora. Its distributional pattern may further differentiate the species-group from other congeners.